Library marketing basics - Polger, Mark Aaron (Rowman & Littlefield, 2019)
Library Marketing Basics is an accessible, step-by-step, easy to understand, and "hands on" resource for any librarian who is interested in learning basic marketing tips to raise the profile of their library. It is designed for beginners who are new to library marketing.